Structure, antioxidant property and protection on PC12 of a polysaccharide isolated and screened from Abelmoschus esculentus L.Moench (okra). Issue 6 (19th March 2022) - Pan, Li-Chao; Sun, Yang-Yang; Zhang, Xiao-Ling; Zhu, Zhen-Yuan; Liu, Chun-Yu; Sun, Hui-Qing; Geng, Xue-Qing; Jiang, Wei; Wang, Jia-He
Abstract: AeP-P-2, a pectic polysaccharide, was extracted from the fruit pod of okra. It composed of rhamnose (Rha), arabinose (Ara), glucose (Glc), galactose (Gal) and galacturonic acid (GalA) with the ratio of 4.75:2.01:1.00:4.91:7.24. The main structural feature of AeP-P-2 are 1, 4-linked galacturonan units (homogalacturonan backbone) and (1 → 2) and (1 → 2, 4) linked Rha (rhamnogalacturonan I region). And the other side chains contained →1)-linked Ara, (1 → 5)-linked Ara, (1 → 4)-linked Glc, (1 → 6)-linked Gal, (1 → 4)-linked Rha, (1 → 2, 4)-linked Rha, →1)-linked Ara and →1)-linked Gal. When the concentration of AeP-P-2 was 3.2 mg/mL, the scavenging rates on DPPH·, ABTS, O 2− · and ·OH reached to 61.88%, 87.10%, 52.17% and 60.32%, respectively. AeP-P-2 also could protect PC12 cells from the damage of H2 O2 and reduce apoptosis caused by oxidative damage by decreasing the level of ROS. The findings indicated that okra was a functional vegetable and AeP-P-2 was worth studying and developing into antioxidant component. GRAPHICAL ABSTRACT: